PENANGANAN VEKTOR PENANGANAN VEKTOR PENYAKIT DBD DUSUN II DESA GONGGONG: PENANGANAN VEKTOR PENYAKIT DBD DUSUN II DESA GONGGONG - Moh Malikul Mulki; Ferry Mangampa; Angga Wahyu Nugroho; Rismawati R. Suleng; Maimuna; Jeni Ester Rosalina Singgal; Siti Salmi Sombili; Panji Hidayat (CV. Multi Kreasi Media, 2022)
Dangue hemorrhagic fever (DHF) is a vector-borne disease caused by the Dangue virus and transmitted by the Aedes sp. This disease is characterized by a sudden fever of 2-7 days without apparent cause, weakness, fatigue, lethargy, restlessness, heartburn, accompanied by skin bleeding in the form of red spots, bruising, rash, sometimes nosebleeds, bloody stools, vomiting blood, consciousness. decline or shock. This disease affects all ages and everyone. Based on the results of the study, it was found that the problem of handling vectors for dengue disease also occurred in hamlet II, Gonggong Village, in this case the efforts made to increase the effectiveness of handling vectors for dengue disease management, work programs that can be made are social services and counseling about the influence of handling vectors for dengue disease with 3 M Plus